Stent Retrievers in Acute Ischemic Stroke: Complications and Failures during the Perioperative Period - Gascou, G. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: Stent retriever–assisted thrombectomy promotes high recanalization rates in acute ischemic stroke. Nevertheless, complications and failures occur in more than 10% of procedures; hence, there is a need for further investigation. MATERIALS AND METHODS: A total of 144 patients with ischemic stroke presenting with large-vessel occlusion were prospectively included. Patients were treated with stent retriever–assisted thrombectomy ± IV fibrinolysis. Baseline clinical and imaging characteristics were incorporated in univariate and multivariate analyses. Predictors of recanalization failure (TICI 0, 1, 2a), and of embolic and hemorrhagic complications were reported. The relationship between complication occurrence and periprocedural mortality rate was studied. RESULTS: Median age was 69.5 years, and median NIHSS score was 18 at presentation. Fifty patients (34.7%) received stand-alone thrombectomy, and 94 (65.3%) received combined therapy. The procedural failure rate was 13.9%. Embolic complications were recorded in 12.5% and symptomatic intracranial hemorrhage in 7.6%. The overall rate of failure, complications, and/or death was 39.6%. The perioperative mortality rate was 18.4% in the overall cohort but was higher in cases of failure (45%; P = .003), embolic complications (38.9%; P = .0176), symptomatic intracranial hemorrhages (45.5%; P = .0236), and intracranial stenosis (50%; P = .0176). Concomitant fibrinolytic therapy did not influence the rate of recanalization or embolic complication, or the intracranial hemorrhage rate. Age was the only significant predictive factor of intracranial hemorrhage (P = .043). CONCLUSIONS: The rate of perioperative mortality was significantly increased in cases of embolic and hemorrhagic complications, as well as in cases of failure and underlying intracranial stenoses. Adjunctive fibrinolytic therapy did not improve the recanalization rate or collateral embolic complication rate. The rate of symptomatic intracranial hemorrhage was not increased in cases of combined treatment.